Lead isotopic characteristics of gun bullets prevailed during the 19th century in Japan: Constraints on the provenance of lead source from the United Kingdom and Japan. (February 2022) - Aizawa, Masataka; Mizota, Chitoshi; Hosono, Takahiro; Shinjo, Ryuichi; Furukawa, Yuki; Nobori, Yoshihiro
Highlights: Gun bullets used in Japan during 19th century were analyzed for lead provenance. Pb isotopic analysis revealed provenances from Japan and the United Kingdom. Spherical gun bullets from domestic Tsushima Island were made in 1811–1839. Lead source of gun bullets changed with its shape during the Boshin War. Opposing armies in the Satsuma Rebellion used gun bullets of different provenance. Abstract: Metal lead constitutes one of the major elements of the common historic firearm's bullets. Since their early development in Medieval China, lead bullets in combination with gunpowder have been consistently used in historical wars worldwide. The increasing demand to produce lead bullets peaked during the 19th century when multiple wars were happening across the world. However, limited information was available for the source of lead bullets, which was revealed on the basis of sample collection from the relevant battlefields during the known historic conflicts. We examined the lead isotopic ( 204 Pb, 206 Pb, 207 Pb, and 208 Pb) compositions of historic bullets common during the early-to-mid-19th century, which were obtained from different areas of Japan to investigate their provenances. Special emphasis was placed on two civil wars, the Boshin War (1868–1869) and the subsequent Satsuma Rebellion (1877, also called the Seinan War), for the source analysis of the bullets. The worldwide isotopic databases of lead ores were used for the comparison. Our results show a potential temporal shift in the source of lead for bullet production. Spherical gun bullets were used until the early stage of the Boshin War, which were suggested to be made from either Japanese domestic lead or lead imported from the United Kingdom. This result implies that the lead from the United Kingdom shared a major worldwide market for exportation during the mid-19th century. However, the share of domestic lead in bullets increased during the later stages of the Boshin War as the style changed from spherical to acorn-shaped (conical–cylindrical soft lead bullets). This suggests that each clan not only imported bullets from abroad but also tried to manufacture bullets themselves during this civil war. Moreover, reflecting the difference in the style of relevant guns (Snider vs. Enfield rifles), two major lead sources were suggested for the bullets used during the time of the Satsuma Rebellion, i.e., Japanese ore lead and lead imported from the United Kingdom. The Pb isotope ratios illustrated the difference of equipment for both armies, namely, that governmental forces exclusively used newer rifle (Snider rifle) with imported gun bullets from the United Kingdom, whereas the rebel army fought using older weapon (Enfield rifle) with bullets manufactured themselves. This study demonstrates that an application of lead isotopic fingerprinting on the basis of regional sample collections provides important evidence for better understanding the relevant socioeconomic regimes that are not able to be fully reconstructed by historians.